Assessment of children’s exposure to air pollutant PM10 and lead in crtitical districts in the Republic of Serbia - Gladović, Ana; Petrović, Bojana; Javorac, Dragana; Buha Djordjević, Aleksandra; Ćurčić, Marijana; Djukic-Ćosić, Danijela; Šoštarić, Andrej; Antonijević, Biljana; Bulat, Zorica (Archives of Pharmacy, 2022)
PM10 particles present in excessive concentrations in polluted air can negatively affect respiratory and cardiovascular system, whereas lead exposure shows adverse effects on renal, hematological, immunological, reproductive and neurological system, especially in children (1). This study was carried out to assess children’s exposure to PM10 and lead through the air in critical districts of Serbia. Mean yearly concentrations of PM10 and lead were used from reports of the Serbian Enviromental Protection Agency, for selected measuring sites in the cities of Subotica, Smederevo, Bor, Valjevo and Kraljevo. Measuring sites were selected based on air quality (over-polluted air) and being close to places where children spend their time during the day. The US EPA method was used to assess health risk, which classifies risk as acceptable (≤1) or unacceptable (>1) based on hazard quotient (HQ) and hazard index (HI) values (2). HQ for PM10 particles was higher than 1 in all critical districts, indicating risk as unacceptable. Values of HI for lead were lower than 1 in all critical districts, indicating risk as acceptable. Results are showing that actions for reduction of air pollution in Serbia should be taken due to obtained results for particulate matter and lead.